An Initial Exploration of Malaysians’ Perceptions of SOSMA 2012 - Dhanapal, Saroja; Sabaruddin, Johan Shamsuddin (Journal of Malaysian and Comparative Law, 2018)
The Security Offences (Special Measures) Act 2012 (SOSMA) was passed by Parliament to replace the old Internal Security Act 1960 (ISA) and was given the royal assent on 18 June 2012. Since SOSMA came into play, it has not laid to rest the ongoing debate of its predecessor the ISA which was contended to be in contravention not only of the Federal Constitution but also the basic principles upheld under the Rule of Law (RoL). SOSMA has been scrutinised and debated upon at various levels both locally and internationally. This study examines the perception of SOSMA by a selected group, focusing on its implication with reference to the ISA, the Malaysian Federal Constitution and the principles upheld under the RoL. The study was conducted by survey questionnaire using a 5-point Likert Scale. Since the whole study was to evaluate perceptions specifically related to the laws in Malaysia, a non-probability purposive sample was selected comprising of lawyers, law lecturers, law students and those who are working in other sectors but with a legal background. The findings indicate that on the whole the respondents were of the opinion that an Act dealing with internal security is essential and required. However, the consensus is that SOSMA needs to be amended as there is a clear indication that it contravenes basic human rights as upheld under the RoL, and that it infringes rights protected under the Federal Constitution. The study ends with a recommendation for the survey to be carried out amidst a larger population and should the findings be similar, the government is then advised to re-examine the SOSMA with a view to retain, amend or repeal the said Act.